Deep time, dark times : on being geologically human - Wood, David, 1946- (Thinking out loud (New York, N.Y.), 2019)
'Deep Time, Dark Times' takes its bearing from Nietzsche's concern that a surfeit of history can extinguish the passion for life, especially when we are reminded of our capacity for cruelty and folly.